Qs. Al-Fatihah Dalam Perspektif Ilmu pendidikan (Kajian Tafsir Tematik) - Ahmad Mujahid; hiljati hiljati (IAI DDI POLEWALI MANDAR, 2022)
Profil beriman, betakwa, berakhlak mulia pada pelajar Pancasila,merupakan aspek penting dalam ajaran agama Islam. Islam mengemas tata cara keberimanan, dan akhlak mulia dalam al-Qur’an dan al-Hadis secara jelas dan rinci. Pada aspek ini tidak lepas dari konsep Pendidikan dalam al-Qur’an. Al-qur’an sebagai pedoman bagi umat Islam juga telah melakukan reformasi terhadap Pendidikan dan memberi pengertian yang luas tentang Pendidikan.Pelajar Pancasila adalah pelajar yang memiliki profil yang terbangun utuh dengan enam dimensi pembentuknya. Dimensi ini antara lain: Beriman, bertakwa kepada Tuhan yang Maha Esa dan berakhlak mulia; Mandiri; Bergotong-royong; Berkebinekaan global; Bernalar kritis; Kreatif. Dari enam dimensi pembentukan profil pelajar Pancasila maka pada dimensi yang pertama berkenaan dengan konsep Pendidikan yang terdapat pada qur’an surat Al-Fatihah. Dimensi beriman, bertakwa kepada Tuhan yang Maha Esa dan berakhlak mulia. Abstract The profile of faith, piety, noble character in Pancasila students, is an important aspect in the teachings of Islam. Islam packages the procedures for belief, and noble character in the Qur'an and al-Hadith in a clear and detailed manner. In this aspect, it cannot be separated from the concept of Education in the Qur'an. The Qur'an as a guide for Muslims has also reformed education and provided a broad understanding of education. Pancasila students are students who have a fully built profile with six dimensions of its formation. These dimensions include: Faith, fear of God Almighty and noble character; Independent; Worked together; Global diversity; Critical reasoning; Creative. Of the six dimensions of forming the Pancasila student profile, the first dimension relates to the concept of Education contained in the Qur'an Surah Al-Fatihah. Dimensions of faith, fear of God Almighty and noble character. Keywords: Al-Fatihah, Educational Science Perspective